2000
DOI: 10.1063/1.126757
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen migration during epitaxial regrowth in Cs+-irradiated α-quartz investigated by means of nuclear reaction analysis

Abstract: The migration of oxygen in ion-beam-amorphized c-SiO2 (α-quartz) was investigated by means of nuclear reaction analysis using the resonant reaction O18(p,α)15N for oxygen depth profiling. Only very small amounts of oxygen were observed to diffuse in crystalline or in Xe+-ion beam-amorphized α-quartz after high-temperature annealing. However, a dramatic migration of oxygen occurs in Cs+-implanted α-quartz in the same temperature range (600–900 °C), where Cs diffuses out of the amorphized layer and epitaxial rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…A similar attempt after proton and nitrogen implantations failed. 5,6 Besides these chemically guided SPEG studies, in which implanted or resident impurities play an important role, Dhar, Bolse, and Lieb 7 have achieved full dynamic SPEG after Ne ion implantation and Wang et al 8 Roccaforte et al [9][10][11][12] studied chemically guided SPEG of ␣-quartz after Cs and Na ion irradiation and annealing in air or an 18 O 2 atmosphere. Similar studies after Li implantation were carried out by Gustafsson et al 13 These studies showed full or partial SPEG to occur up to temperatures of about 1170 K. The temperature at which the alkali atoms become mobile and the recrystallization process starts was found to correlate with the fluence and size of the implanted alkali ions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar attempt after proton and nitrogen implantations failed. 5,6 Besides these chemically guided SPEG studies, in which implanted or resident impurities play an important role, Dhar, Bolse, and Lieb 7 have achieved full dynamic SPEG after Ne ion implantation and Wang et al 8 Roccaforte et al [9][10][11][12] studied chemically guided SPEG of ␣-quartz after Cs and Na ion irradiation and annealing in air or an 18 O 2 atmosphere. Similar studies after Li implantation were carried out by Gustafsson et al 13 These studies showed full or partial SPEG to occur up to temperatures of about 1170 K. The temperature at which the alkali atoms become mobile and the recrystallization process starts was found to correlate with the fluence and size of the implanted alkali ions.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the regrown crystalline layer improved with the increasing size ͑Li→Na→Cs͒ of the alkali ions. [9][10][11][12][13][14] However, in these studies, the influence of several experimental parameters and the surface morphology was never investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic mechanism of epitaxial regrowth of ionirradiated quartz has been discussed by Roccaforte et al [6][7][8] using ideas developed by Spaepen, Turnbull, and others [14][15][16][17]. It is noteworthy that, in all the cases with implanted alkali ions studied so far, the epitaxy of the amorphized layer, the out-diffusion of the alkali ions, and the oxygen exchange between the SiO 2 matrix and the annealing gas are highly correlated [4,6].…”
Section: Epitaxymentioning
confidence: 99%
“…Since doping quartz by ion beam implantation disturbs or even destroys its crystalline long-range order, many attempts at solid-phase epitaxial regrowth of the damaged/amorphized layers by means of dynamic, chemical, or laser-annealing epitaxy have been made [4][5][6][7][8]. Alkali-ion implantation of α-quartz followed by thermal annealing in air or oxygen, a process called chemical epitaxy, indeed provides complete epitaxy around 1100 K [4,[6][7][8][9][10][11]. The recrystallization is accompanied by alkali out-diffusion and oxygen exchange between the annealing gas and the matrix, as verified by Rutherford backscattering channeling spectroscopy (RBS-C) and time-of-flight elastic recoil detection analysis (TOF-ERDA) after annealing the samples in 18 O 2 tracer gas [4, 6-8, 10, 11].…”
Section: Introductionmentioning
confidence: 99%